2009
DOI: 10.1007/s00709-009-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biochemical evaluation of cadmium tolerance mechanism in callus and seedlings of Brassica juncea

Abstract: In vitro grown callus and seedlings of Brassica juncea were treated with equimolar concentrations of cadmium and compared for their respective tolerance to cadmium. Calli cultures were grown on Murashige and Skoog medium supplemented with alpha 6-benzyl aminopurine (200 microg (-1), naphthalene acetic acid 200 microg L(-1)) and 2,4-dichloro-phenoxy acetic acid (65 microg L(-1)) while the seedlings grown on Hoagland's nutrient solution have been carried out. Cellular homeostasis and detoxification to cadmium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
40
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 36 publications
9
40
0
1
Order By: Relevance
“…Thus this reduction might be accompanied by the accumulation of H2O2 in different compartments which may cause the inactivation of this enzyme (Vitoria et al, 2001). Similar trends in the SOD activity under Cd stress had been observed in Sesbania drummondi callus (Israr et al, 2006), B. juncea callus (Shekhawat et al, 2010) and the adapted calli of sunflower and safflower (Gallego et al, 2002;Namjooyan et al, 2012). Catalase (CAT) is another integral component of antioxidant system and its role in protecting the organism from damage caused by ROS is indispensable.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Thus this reduction might be accompanied by the accumulation of H2O2 in different compartments which may cause the inactivation of this enzyme (Vitoria et al, 2001). Similar trends in the SOD activity under Cd stress had been observed in Sesbania drummondi callus (Israr et al, 2006), B. juncea callus (Shekhawat et al, 2010) and the adapted calli of sunflower and safflower (Gallego et al, 2002;Namjooyan et al, 2012). Catalase (CAT) is another integral component of antioxidant system and its role in protecting the organism from damage caused by ROS is indispensable.…”
Section: Discussionsupporting
confidence: 51%
“…Tissue culture techniques offer valuable tool for studying, testing, improving and selecting plant material for tolerance to stress factors and cellular stress response (Azevedo et al, 2005;Shekhawat et al, 2010;Ahmad et al, 2013). This evaluation of the behaviour of in vitro cell cultures exposed to Cd toxicity may contribute to the knowledge that these cells may used in genetic improvement programs to withstand Cd toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Each value represents the mean±SE. Control plants were grown on Hoagland's nutrient solution as control, NaCl plants were stressed by 150 mM NaCl, oligochitosan plants were pretreated with 0.0625% oligochitosan solutions, oligochitosan-NaCl plants were pretreated with 0.0625% oligochitosan and then stressed by 150 mM NaCl for encoding SOD (Bowler et al 1992;Shekhawat et al 2010). Higher activity of SOD is an indication of efficient detoxification of superoxide radical (Abraham and Dhar 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, comparative evaluation of cadmium (Cd) tolerance mechanisms was performed in callus and seedlings of B. juncea. The study found calli to be more tolerant to Cd-induced oxidative stress (Shekhawat et al 2010). Yang et al (2007) evaluated As accumulation and responses in calli of Pteris vittata and Arabidopsis thaliana and reported that P. vittata calli accumulated more As, tolerated higher AsV concentrations, and showed lower toxicity as compared with the calli of A. thaliana.…”
Section: Introductionmentioning
confidence: 98%